MO828INTENSIFIED TREATMENT FOR PREGNANCY IN HEMODIALYSIS PATIENTS, ANALYSIS OF 13 CASES: IS THERE A GENDER ADVANTAGE?. (29th May 2021) - Marcelli, Daniele; Rybakova, Olga; Shilo, Valery; Wohn, Luisa; Barth, Claudia
Abstract: Background and Aims: Pregnancy in dialysis patients is rare but challenging for nephrologists and obstetricians, because pregnancy has a significant maternal and fetal risk in these patients. Although intensified hemodialysis is effective to achieve favorable clinical outcomes, the evidence concerning reliable parameters for the optimal dialysis prescription is scarce. Herein, we report the management on hemodialysis and outcome of pregnancies occurring in the B. Braun dialysis network in Russia. Method: We performed retrospective analysis of all pregnancy cases in B. Braun dialysis chain in Russia from 2013 to 2020. Cases were reported by the involved Renal Care Centers by a common questionnaire. All patients were treated with B. Braun Dialog+, AV set Dialog +, SolCart bicarbonate cartridge and Xevonta dialyzers. Results: 13 pregnancies were reported, all achieved without infertility treatment: 1 was interrupted by voluntary termination of pregnancy, 9 resulted with living birth (6 females and 3 males) after a mean of 24 gestational weeks (7 cesarean and 2 vaginal deliveries), 2 with stillbirth and 1 with spontaneous abortion after 8 gestational weeks. Mothers with positive pregnancy outcome were significantly younger (27.9±5.1 vs. 36.3±5.6 years), without differences in dialysis vintage, previous successful or unsuccessful pregnancies and during follow-up blood pressure was well controlled. Females newborns had borderline significant greater body weight (1.9±0.6 vs. 1.1±0.1 kg, p=0.076). 5 newborns had respiratory distress syndrome, 1 jaundice. Conclusion: : Prompt increase of treatment frequency and time on high-flux/HDF dialysis were associated with successful pregnancy outcome. Considering that cardiovascular system and endogenous metabolism dynamically alter during pregnancy, various clinical parameters, i.e. body weight and blood pressure, should be closely monitored to modify dialysis settings accordingly. Female gender of the newborn seems to be associated with a better outcome. This study shows the safety of high-flux hemodialysis and hemodiafiltration treatments in pregnancy and the benefit of enhanced prescription in dialysis time and frequency. Acknowledgement: The authors express their gratitude to the entire medical multidisciplinary team from B. Braun Russia Renal Care Centers and other local medical institutions directly and indirectly involved in the treatment of each case described.